Smoking Behavior Among Adolescents at A Public Junior High School - Syam, Sadli; Sukirman, Putri Maharani; Firmansyah, Firmansyah; Lestari, Ayu; Suwendro, Novi Inriyanny (Media Publikasi Cendekia Indonesia, 2023)
The purpose of this study is to determine smoking behavior among adolescents, particularly in a public junior high school of SMP Negeri 9 Palu City. This type of research was qualitative research with a case study approach. The informants in this study consisted of 10 people using a purposive sampling technique. The variables in this study consisted of knowledge, attitudes, facilities and infrastructure, and peers. The results showed that knowledge of smoking behavior was quite good regarding the dangers of smoking. The attitude of most of the informants towards smoking behavior was not good because they still accepted peer invitations to smoke. Access to cigarettes is quite easy by buying retail cigarettes at stalls near the school. Peers have a major influence on smoking behavior at school. Adolescents at SMP Negeri 9 Palu City, despite having good knowledge about the dangers of smoking, demonstrate inconsistent behavior due to positive attitudes, easy access to cigarettes, and strong peer influence. This highlights the need for interventions that address not only knowledge dissemination but also address attitudes and peer pressure, making it harder to access cigarettes near schools.